Design and Development of a Web-Based Thermal Application for Vapor Compression Refrigeration Systems - Ratu Yanra Dewi; Muhamad Yulianto; Mohamad Solahudin; Leopold Oscar Nelwan; Ida Afriliana; Roni Darpono; N Nasruddin (The University of Lampung, 2026)
The growth of the global food industry has led to an increased demand for cold storage systems to maintain product quality. Cold storage systems based on the vapor compression cycle offer high energy efficiency. However, their design involves multiple stages, ranging from cooling load calculations to prototype development for performance evaluation. This study integrates digital twin–based thermal simulation with Life Cycle Climate Performance (LCCP) analysis into a single web-based platform, namely THE POCI, for cold storage design. The application allows system design, performance calculation, and estimation of the system emission. The development process followed the System Development Life Cycle (SDLC) methodology. Functional testing was conducted using Black-box Testing, while user evaluation was performed using the System Usability Scale (SUS). The results show that all modules provide the expected information and can be used effectively. Model validation against experimental data resulted in Mean Absolute Percentage Error (MAPE) values of 11% for compressor power, 17% for cooling capacity, and 14% for the coefficient of performance (COP). User evaluation involving 47 respondents across the four modules yielded a SUS score of 64.41, indicating that the application is well accepted and has an adequate level of usability.